Cultural Structuring of Urok Practice: An Intercultural Communication of the Bago Tribe in Kalinga Province, Philippines - Manera; B, Alma; Vecaldo; T, Rudolf; Saquing; B., Jasmin (International Journal of Psychosocial Rehabilitation, 2020)
Intercultural communication analysis of the cultural structuring of the Urok practice of the Bago tribe in Kalinga Philippines forms a community identity, which is deserving of acceptance and respect from individuals outside the tribe. Urok is a practice of extending financial help to every member of the tribe during marriage, hospitalization, and death. In this study, cultural structuring of the Urok practice of the Bago tribe was analyzed through intercultural communication. It investigated how the members of the indigenous community lend meaning to their first-hand experience in exemplifying the Urok practice particularly its relevance in easing members of the community during their financial difficulties. Using qualitative research design employing in-depth interview, twelve (12) informants were selected through purposive sampling. The interview data were transcribed, treated through open coding, and thematically analyzed. Significant findings included themes as follow: (a) Urok as socio-cultural sense of genuine mutual love and value for co-existence, (b) Urok is not only seen as material assistance but as a picture of harmonious relationship, and (c) Urok as a form of moral sympathy and a solid, binding action of love. Generally, an intercultural communication of the Bago tribe is revealed in Urok practice that is culturally structured creating the image of Bago’s solidarity and mutuality. Undoubtedly, Urok becomes a significant piece of the community life since it is ingrained in the value of “panakikadwa” (companionship) that engenders reciprocity and camaraderie.